Production, acceptability, and online comprehension of Spanish differential object marking by heritage speakers and L2 learners - Regulez, Begoña Arechabaleta; Montrul, Silvina (Frontiers in Psychology, 2023)
We analyzed the production, acceptability and online comprehension of Spanish differential object marking (DOM) by two groups of bilingual speakers living in the U.S.: heritage speakers and L2 learners. DOM is the overt marking of direct objects that are higher on the animacy and referentiality scales (Aissen, 2008), such as animate and specific objects in Spanish, marked by the preposition a (Juan ve a María ‘Juan sees DOM María’). Previous studies have reported variability and high omission rates of obligatory DOM in bilingual situations where Spanish is in contact with a non-DOM language (Montrul & Sánchez-Walker, 2013; Sánchez, 2003). Our study combined different methodologies to tap knowledge of DOM in the two groups. The results showed that heritage speakers and L2 learners exhibited variability with DOM in production and comprehension and processing; 2) can integrate DOM into their production, judgments and processing, but they do so inconsistently and 3) type of task and type of sentence each have an effect on speakers’ use of DOM.